Static balancing behaviour of the mandible - Hellmann, Daniel; Brüstle, Fabian; Terebesi, Sophia; Giannakopoulos, Nikolaos Nikitas; Eberhard, Lydia; Rammelsberg, Peter; Schindler, Hans J. (European journal of oral sciences, 2015)
The objective of this study was to investigate the mechanisms of physiological control of the craniomandibular system during force-controlled biting: in intercuspation, restricted by predetermined anatomic-geometrical conditions [i.e. biting in intercuspation (BIC)]; and on a hydrostatic system [i.e. auto-balanced static equilibrium of the mandible (BAL)], in which the mandible is balanced under unrestricted occlusal conditions. For 20 healthy subjects, the spatial positions of the condyles, the lower molars, and the incisal point were measured, and the electromyographic (EMG) activity of the musculus masseter and musculus temporalis anterior were recorded bilaterally, during force-controlled biting (50, 75, 100 N) on a hydrostatic device. The results were compared with those obtained during BIC. During BAL, the neuromuscular system stabilizes one condyle, so it behaves as a virtual fulcrum, and all available biomechanical degrees of freedom of the opposite side are used to achieve a bilaterally equal vertical distance between the upper and lower dental arches. The variability of the positions of the molars was significantly smaller than for the condyles. The EMG co-contraction ratios calculated for homonymous muscle regions revealed significant differences between BIC and BAL, specifically, greater symmetry during BAL with substantial asymmetry of approximately 25% remaining. In conclusion, the results revealed precise neuromuscular control of the position of the lower dental arch; this information might form the basis for interference-free tracking of the mandible in intercuspation under different conditions.